Implikasi Faktor Internal dan Eksternal terhadap Return Saham pada Perusahaan yang Terdaftar di Jakarta Islamic Index - Nabilla Permata Suci; Tripuspitorini, Fifi Afiyanti; Barnas, Benny; Tamara, Destian Arshad Darulmalshah (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The purpose of this study is to determine the influence of internal and external factors on stock returns for the 2017-2022 period. The population of this research is companies listed in the Jakarta Islamic Index (JII). The sample data was determined by the purposive sampling method and produced twelve companies. In this study, secondary data were used CR, DER, EPS obtained from the annual financial statements for the 2017-2022 period which have been published through the official website of each company, inflation data obtained from the website of Bank Indonesia. The analysis methods used, namely panel data regression. The data processing tool used in this research is Eviews. The results of this study prove that partially the DER has an effect on stock returns, while the CR, EPS and inflation partially have no effect on stock returns. Simultaneously, the CR, DER, EPS and inflation have no effect on stock returns.